The invasive hydromedusae Blackfordia virginica Mayer, 1910 (Cnidaria: Blackfordiidae) in southern Brazil, with comments on taxonomy and distribution of the genus Blackfordia - Bardi, Juliana; Marques, Antonio Carlos (Zootaxa, 2009)
The invasive brackish-water hydrozoan Blackfordia virginica is reported from estuaries and harbours in southeastern and southern Brazil. Medusae of the species were collected for the first time in Cananéia, Guaratuba Bay, and Babitonga Bay. They were also found in Paranaguá Bay where they were previously known to occur. Based on material examined here, a comparative redescription is given of B. virginica, and its distribution worldwide is reviewed. The three nominal species of Blackfordia are assessed.